2003
DOI: 10.22358/jafs/67762/2003
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of BTN and GHR genes and its impact on bulls’ breeding value for milk production traits

Abstract: The aim of the study was to estimate the effect of the butyrophilin (BTN) and growth hormone receptor (GHR) gene polymorphisms on the breeding value of genotyped AI bulls for milk production traits. A total of 131 Holstein-Friesian bulls were analysed. The following allele frequencies have been found: 0.88 (L) and 0.12 (A) at the BTN locus, and 0.85 (S) and 0.15 (G) at the GHR locus. The effect of genotype on milk yield and composition was tested in the group of 101 AI proven bulls. Because the number of A/A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The frequencies of the minor allele R and the rare genotype KR of the BTN1A1 polymorphism were 6.21 and 12.41%, respectively. The allele frequencies in our Czech Fleckvieh cows were close to the results observed by Komisarek and Dorynek (2003) in Holstein cattle (12%) and Sadr et al (2008) in the Najdi cattle population (14%). Zegeye et al (1999) did not reveal a relationship between K468R polymorphism and milk production in five grand-sire Holstein families.…”
Section: Resultssupporting
confidence: 90%
“…The frequencies of the minor allele R and the rare genotype KR of the BTN1A1 polymorphism were 6.21 and 12.41%, respectively. The allele frequencies in our Czech Fleckvieh cows were close to the results observed by Komisarek and Dorynek (2003) in Holstein cattle (12%) and Sadr et al (2008) in the Najdi cattle population (14%). Zegeye et al (1999) did not reveal a relationship between K468R polymorphism and milk production in five grand-sire Holstein families.…”
Section: Resultssupporting
confidence: 90%
“…These were in correspondence with earlier reported frequencies of BTN1A1 allele as 0.875 and 0.125 (Taylor et al 1996a), 0.85 and0.15 (Husaini et al 1999), 0.84 and 0.14 (Sadr et al 2008), 0.88 and0.12 (Komisarek andDorynek 2003), 0.87 and 0.13 , 0.69 and 0.31 (Muszyńska et al 2010) in different milch bovines. Highest frequency was observed for AA genotype and A allele whereas lowest frequency was found for BB genotype and B allele.…”
Section: Resultssupporting
confidence: 92%
“…Bovine butyrophilin gene consists of 8 exons and 7 introns and is located on the 23 rd chromosome (Ashwell et al 1996). BTN1A1 is possibly QTL candidate gene affecting milk yield and composition in dairy animals (Komisarek and Dorynek 2003). Franke et al (1981) suggested that butyrophilin is widely expressed during lactation and is specific to mammary tissue.…”
Section: Introduc Onmentioning
confidence: 99%
“…T h e frequency of dominant allele K in different studies were0.88 by Komisarek and Dorynek (2003), 0.83 by Bhattacharya et al (2006), 0.86 by Sadr et al (2008), 0.88 by Rengarajan (2011), 0.89 by Vishwanath (2014) and 0.86 by Al-Waith (2019). Thus, the results of K allele dominance was in accordance with all aforementioned studies.…”
Section: High Resolution Melt Curve Analysismentioning
confidence: 90%